The Effect of Pressure to the Crystallization and Glass Transition Temperature of Liquid PdSi Alloy Modelled with Quantum Sutton-Chen Potential - Kazanç, Sefa; Canbay, Canan Aksu (My University, 2019)
In this work, the effect of pressure on the crystallization (Tc) and glass transition (Tg) temperatures of a modelledPdSi liquid alloy was investigated for different cooling rates by using Quantum Sutton Chen(K-SC) potentialwhich is used to determine the interactions between atoms. It was determined that at the cooling rates of 2,5x1011K/s and 2,5x1012 K/s the alloy system in liquid phase transformed into crystal and amorphous phase, respectively.The glass transition temperature was defined by the Wendt-Abraham parameter and radial distribution function(RDF) peaks. It was concluded that the increment of pressure led to an increase in the crystallization and glasstransition temperatures and the ratio of Tg/Tm resulted in an improvement of the glass forming ability.
Keywords: Fizik; Uygulamalı; Nanobilim ve Nanoteknoloji; Fizik; Atomik ve Moleküler Kimya